2021
DOI: 10.21203/rs.3.rs-271642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Visual outcome in Post Fever Retinitis: A Retrospective Analysis

Abstract: Purpose: To identify the predictors of final visual outcome in cases with post fever retinitis (PFR).Methods : This is a retrospective study of cases with diagnosis of post fever retinitis. Color fundus photograph and optical coherence tomography (OCT) parameters at presentation and final visit were analysed. Various factors at presentation [age, systemic illness, best corrected visual acuity (BCVA), area of retinitis and hard exudates, OCT parameters], at final visit (optic disc pallor, OCT parameters) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…The OCT parameters predicting visual outcomes in ER have been very recently reported by Biswal et al . [ 7 ] As in their study, we also found subfoveal deposits and optic disc pallor responsible for poor visual outcomes. In addition to those factors, they have also found the height of subretinal fluid at presentation as one of the contributory factors.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The OCT parameters predicting visual outcomes in ER have been very recently reported by Biswal et al . [ 7 ] As in their study, we also found subfoveal deposits and optic disc pallor responsible for poor visual outcomes. In addition to those factors, they have also found the height of subretinal fluid at presentation as one of the contributory factors.…”
Section: Discussionsupporting
confidence: 73%
“…As demonstrated in Group B despite high CMT and retinitis lesion within 1500 μm of the foveal center, the eyes had better visual outcomes. Biswal et al .’s[ 7 ] study found no statistically significant correlation between age, systemic illness, the interval between fever and retinitis, area of retinitis, different treatment modalities, and the final visual gain. This is in contrast with our findings that older age, diabetic status, and delayed ophthalmic checkups had a significant correlation with the final visual outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation